(untitled) (Nepalese Journal of Management Research, 2021)
Objective: To identify and evaluate the impact of human resource practices on organization performance in service sector. Methods and Materials: Two main sources of data namely primary and secondary were used in the study. The primary data were collected through mail questionnaire method from 132 employees of Nepal Telecom organization for the study. The secondary source was through journals, textbooks and annual reports of Nepal Telecom. After collecting responses from 132 respondents, the data were analyzed through SPSS. The value of Cronbach’s Alpha (α) of overall questionnaire is 0.84, which suggests the reliability of primary data. Descriptive as well as explorative research designs were used to analyze the primary and secondary data. Results and Conclusion: The coefficient of determination between human resource practices and organization performance is 70.89%. There is strong correlation among all independent and dependent variables. All three independent variables are significant positive impact on dependent variable. The study concluded that there is a positive relationship between human resource practices and organization performance of Nepal Telecom organization.